Pengaruh Faktor Spasial Dan A-Spasial Terhadap Preferensi Masyarakat Kampung Tambak Lorok Tinggal Di Rumah Susun - Argiean Luthfi; Nany Yuliastuti (Jurusan Perencanaan Wilayah dan Kota, 2017)
Slums are an urban problem that is always faced by big cities in Indonesia. Addressing the issue, the government has planned a policy of 100-0-100. Implementation of 100-0-100 program in Semarang City is by launching Kampung Tambak Lorok area as a marine kampong area. One of the implementation of maritime villages concept is by building flats. Researchers understand the need for a review of the factors that affect people's preferences to live in a flat house. It is hoped that this study can produce the right policy formulation for the development of apartment project. The purpose of this study is to examine the influence of spatial and a-spatial factors on the preferences of Tambak Lorok villagers to live in flats. The approach used in this research is quantitative approach. This research uses multiple linear regression analysis technique. Based on the results of analysis it is known that the resulting regression equation is Y '= 22.366 + 0.127A1 + 0,183A3 + 0,246B2 + 0,096B5 + 0,054B6 + 0,076B8. Based on these results variables to be considered as the degree of influence are 1) the security of the disaster; 2) spacing of shopping; 3) distance to the main road; 4) completeness of space; 5) unit price; And 6) unit area